Microstructure and mechanical properties of Fe-Si-Ti-(Cu, Al) heterostructured ultrafine composites - Park, J. M.; Kim, D. H.; Mattern, N.; Kim, K. B.; Fleury, E.; Eckert, J. (ELSEVIER SCIENCE SA, 2011)
The influence of partial substitution of Fe by Cu or Al in Fe(75-x)Si(15)Ti(10)(Cu, Al)(x) (x = 0 and 4) ultrafine composites on the microstructure and mechanical properties has been investigated. The Fe(71)Si(15)Ti(10)Cu(4) ultrafine composite exhibits a favorable microstructural evolution and improved mechanical properties, i.e., large plastic strain of similar to 5% and pronounced work hardening characteristics. The mechanical properties of the ultrafine eutectic composite are strongly linked to the length scale heterogeneity and the distribution of the constituent phases. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: NANOSTRUCTURE-DENDRITE COMPOSITE; HIGH-STRENGTH; COMPRESSIVE PROPERTIES; ENHANCED PLASTICITY; BULK ALLOYS; DUCTILITY